Percutaneous Screw Fixation of Slipped Capital Femoral Epiphysis Using Biplanar Fluoroscopy - Emilio Feijoo, BS; Michael J. Conklin, MD (Journal of the Pediatric Orthopaedic Society of North America)
Percutaneous screw fixation for slipped capital femoral epiphysis (SCFE) is a standard surgical procedure. This can be performed on a radiolucent “flattop” table or a fracture table, which holds the leg stable and can help with the serendipitous reduction of unstable SCFE's. Pivotal to success is accurate screw placement in the center of the epiphysis, adequate threads crossing the physis, and avoidance of screw penetration into the joint. Adequate fluoroscopic visualization in all planes is essential. We have used simultaneous biplanar fluoroscopy for accurate screw placement on a fracture table. The indications, techniques, pearls, and pitfalls of this procedure are presented in this study. Key Concepts: (1) Percutaneous screw fixation of SCFE is a mainstay of treatment. (2) Simultaneous biplanar fluoroscopy facilitates accurate screw placement. (3) Positioning on a fracture table can promote incidental reduction in cases where this is desirable. (4) Meticulous attention to room setup, patient positioning, and operative technique are necessary for success.